Sosialisasi Keamanan Digital: Peningkatan Kesadaran Pemuda Karang Taruna 'Cipta Karya' Terhadap Ancaman Siber Dan Perlindungan Diri Di Dunia Maya - Alessandro; Alvin Diaz Setyadi; Altaf Ghani S; Fransiskus N E; Muhammad Dabit H A; Muhamad Fauzan Rusby K; Noufal Maulana; Ryandanu W P; Sadam Alifio; Januardy Ahda S M; Riky Susanto (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Community Service (PKM) activity with the theme "Digital Security Socialization: Increasing Awareness of Youth of Karang Taruna 'Cipta Karya' towards Cyber ​​Threats and Self-Protection in Cyberspace" was carried out by a team of Pamulang University students in Rancagong Village, Legok District, Tangerang Regency, Banten, on November 10, 2024. This program aims to increase public understanding and awareness, especially Karang Taruna youth, regarding cyber threats and digital protection measures. This activity includes delivering educational materials on types of cyber threats such as hacking, online fraud, and data theft, as well as basic techniques for protecting personal information. In addition to delivering the material, interactive sessions in the form of questions and answers and quizzes were also held to encourage active involvement of participants. The results of this activity showed that participants gained a better understanding of the importance of maintaining digital security and were motivated to apply this knowledge in their daily lives. In closing, souvenirs were given to partners as a form of appreciation for their support for this program. This program is expected to continue in the future to reach more communities, so that the younger generation is better prepared to face the challenges of the digital era wisely and safely.